2020
DOI: 10.3390/molecules25122864
|View full text |Cite
|
Sign up to set email alerts
|

Active Compound of Pharbitis Semen (Pharbitis nil Seeds) Suppressed KRAS-Driven Colorectal Cancer and Restored Muscle Cell Function during Cancer Progression

Abstract: Kirsten rat sarcoma viral oncogene homolog (KRAS)-driven colorectal cancer (CRC) is notorious to target with drugs and has shown ineffective treatment response. The seeds of Pharbitis nil, also known as morning glory, have been used as traditional medicine in East Asia. We focused on whether Pharbitis nil seeds have a suppressive effect on mutated KRAS-driven CRC as well as reserving muscle cell functions during CRC progression. Seeds of Pharbitis nil (Pharbitis semen) were separated by chromatography and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the case of AKT, serine phosphorylation (S473) was upregulated in CRC. Some studies revealed that harmine [ 151 ], ophiopogonin D [ 154 ], and luteolin [ 157 ] were able to downregulate this specific serine phosphorylation, while others such as coumarins [ 119 ], resveratrol [ 125 ], quercetin [ 140 ], secoisolariciresinol diglucoside [ 145 ], lycopene [ 158 ], and some plant extracts decrease protein phosphorylation [ 168 , 169 ]. Similarly, in PI3K and BCL2 proteins, quercetin, secoisolariciresinol diglucoside, and iodine-biofortified lettuce extract downregulated their phosphorylation, respectively [ 140 , 145 , 164 ].…”
Section: Nutrigenomic Effects Of Plant-based Dietary Components On Pr...mentioning
confidence: 99%
“…In the case of AKT, serine phosphorylation (S473) was upregulated in CRC. Some studies revealed that harmine [ 151 ], ophiopogonin D [ 154 ], and luteolin [ 157 ] were able to downregulate this specific serine phosphorylation, while others such as coumarins [ 119 ], resveratrol [ 125 ], quercetin [ 140 ], secoisolariciresinol diglucoside [ 145 ], lycopene [ 158 ], and some plant extracts decrease protein phosphorylation [ 168 , 169 ]. Similarly, in PI3K and BCL2 proteins, quercetin, secoisolariciresinol diglucoside, and iodine-biofortified lettuce extract downregulated their phosphorylation, respectively [ 140 , 145 , 164 ].…”
Section: Nutrigenomic Effects Of Plant-based Dietary Components On Pr...mentioning
confidence: 99%
“…Up to 40% of KRAS mutations occur in patients with CRC ( Arrington et al, 2012 ). The discovery of small-molecule RAS inhibitors or a siRNA targeting RAS displayed anti-proliferative activity on xenografts of human CRC cell line SW480 ( Song et al, 2020 ). The mutations of KRAS result in the hyper-activation of RAS-extracellular signal-regulated kinase (ERK) pathway involving transformation of cells and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of Pharbitis nil (L.) Choisy, a traditional plant used in East Asia to treat inflammation and cancer, were used in cell models of colorectal cancer to evaluate the antiproliferative effects of the purified extract [ 6 ]. Cell cycle modulation and apoptosis induction were observed, with changes in the RAS/ERK and AKT/mTOR pathways.…”
mentioning
confidence: 99%